THE PROFESSIONALIZATION OF THE COMMUNITY HEALTHCARE ASSISTANT FROM THE PERSPECTIVE OF HEALTH PROMOTION - Bruna Muller; Dayana Barradas; Maria Antonia Ramos Costa; Mariele da Silva Cambiriba (Universidade Federal do Paraná, 2012)
This study aimed to clarify, through reflection of a bibliographical and documental nature, the importance of the community healthcare assistant as an educator and health promoter in the community. These professionals have acquired great relevancy in the primary healthcare scenario, by acting as health promoters capable of bringing about changes in habits in families and effective social control, this being supported by political and legal conditions to take place. This reflection indicates that the community healthcare assistant's stance regarding families must be more innovative and reflexive, promoting a critical but active attitude to routine situations related to health.